Religion, extremism and violence in South Asia - Ahmed, Imran; Ahmed, Zahid Shahab; Brasted, Howard; Akbarzadeh, Shahram (Politics of South Asia, 2022)
Intro -- Acknowledgements -- Contents -- Notes on Contributors -- List of Figures -- List of Tables -- 1 Introduction -- II -- III -- IV -- 2 Colonial Transformations, Postcolonial Afterlives: Extremism, Exclusion and Distrust in India and Pakistan -- Introduction -- Orientalism and the Colonisation of Indian Religions -- The Coloniality of the Postcolonial -- Religious Extremism in Pakistan: Exclusion, Distrust and State Power -- Religious Extremism in India: History, Communalism and Violence -- Conclusion -- 3 Religion, Extremism and Buddhist-Muslim Relations in Sri Lanka -- Introduction -- The Context of Collective Identity and Religious Extremism in Sri Lanka -- Buddhist-Muslim Relations in Sri Lanka: The Historical Context -- Sinhala Buddhist Nationalism, Religious Extremism and Anti-Muslim Movements -- Political Conditions: The Religion-Political Nexus -- Conservative Religious Ideology and Moral Policing of BBS -- Muslims: Labelled from Social Others to Extremist Groups -- Muslim Political Consciousness, Conservative Islam and the Rise of Radicalism -- Muslim Political Parties and the Missed Opportunity for Religious and Cultural Reforms -- Diffusion of Conservative Islam, Rise of Radicalism and Self-Alienation of the Muslim Community -- Economic Roots of Religious Violence, Social Isolation and Anti-Muslim Narratives -- Conclusion -- 4 Social Media and Hindu Extremism in India -- Introduction -- Part One-Hindutva in Indian Political Discourse -- Hindutva's Cultural Nationalism -- Hindutva and the Modi/BJP Election Campaign -- The Politics of Cow Protection -- Love Jihad -- Ghar Wapsi -- Part Two-Social Media and Hindu Extremism -- Conclusion -- 5 Ram Was a Prophet Too: Syncretism as a Hindu Nationalist Political Strategy -- The Limits of Syncretism -- Syncretism in India -- Manch Syncretism -- Producing Syncretism.